2019
DOI: 10.11648/j.jfa.20190704.12
|View full text |Cite
|
Sign up to set email alerts
|

Dividend Policy and Firm’s Profitability: Evidence from Ethiopian Private Insurance Companies

Abstract: In many rapidly growing economies and emerging markets like Ethiopia, the insurance companies are expected to play a crucial role. The dividend decision is one of the critical financial managementdecisions for firms. Dividend decision is also among the widely addressed and controversial issue in field of finance. The inconclusiveness of dividend theories and empirical studies on the relationship between firm's profitability and dividend payout decisions is one of the most debatable topics inresearches. Hence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…Dividend yield has a positive and insignificant nexus with profitability, which indicates that higher or lower dividend yield has no relation with profitability. This result contradicts the findings of a prior study by Adimasu (2019). Similarly, the retention ratio has a direct and significant link with profitability that shows a lower or (higher) retention ratio has a positive direct relation to lower or (higher) profitability.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Dividend yield has a positive and insignificant nexus with profitability, which indicates that higher or lower dividend yield has no relation with profitability. This result contradicts the findings of a prior study by Adimasu (2019). Similarly, the retention ratio has a direct and significant link with profitability that shows a lower or (higher) retention ratio has a positive direct relation to lower or (higher) profitability.…”
Section: Resultscontrasting
confidence: 99%
“…Meanwhile, dividend payout ratio and corporate size boost share prices. Adimasu (2019) found that dividend payout ratio and company size directly affect profitability. Leverage and tangibility negatively impact return on assets.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…In Ethiopia a lot of research has been done on financial institutions profitability with different statistical models and researchers. For instance, Bernabas (2018), Habtamu and Teferi (2020), Abate (2012), Daniel and Tilahun (2013) all studied by using internal factors and have not considered external factors like macroeconomic (gross domestic products, Inflation). And similarly, Sambasivam and Ayele (2013), Yuvaraj and Abate (2013), studied firm-specific factors but they also ignored macroeconomic factors affecting profitability.…”
Section: Introductionmentioning
confidence: 99%
“…Companies need to continue to maintain the availability and adequacy of working capital because it is related to liquidity which is the lifeblood of a company [8]. In fact, working capital management is very important because it impacts a company's liquidity and profitability [9]. It is said that companies need to maintain a balance between liquidity and profitability because high liquidity can mean low risk and low profitability, and vice versa [10].…”
Section: Introductionmentioning
confidence: 99%